Driver glare exposure with different vehicle frontlighting systems. (February 2021) - Alcón Gil, Patricia; De Santos-Berbel, César; Castro, Maria
Highlights: A line-of-sight analysis by analogy with ray of light was used to assess glare. A greater glare incidence is produced as the horizontal spread angle increases. Swiveling headlights increase glare on left curves and reduce it on right curves. Glare evaluation assists in deciding whether to place a vegetation barrier and where. Abstract: Introduction: Highway safety performance at night has received less attention in research than daytime, despite the higher accident rates occurring under night-time conditions. This study presents a procedure to assess the potential hazard for drivers created by headlight glare and its interaction with the geometric design of highways. Method: The proposed procedure consists of a line-of-sight analysis performed by a geoprocessing model in geographic information systems to determine whether the rays of light that connect headlights and oncoming drivers are obstructed by either the roadway or its roadsides. Then, the procedure checks whether the non-obstructed rays of light are enclosed by a given headlight beam. Different hypotheses were set concerning the headlight beam features, including the horizontal spread angle and whether the headlights are fixed or swiveling. A highway section was selected to test and validate the procedure proposed. A 3D recreation of the highway and its environment derived from a LiDAR point cloud was used for this purpose. Results: The findings disclose how glare is produced on tangents, horizontal curves, transitions between them and sequences of curves. The effect of visual obstructions conveniently placed is also discussed. Conclusions: A greater glare incidence is produced as the horizontal headlights spread angle increases. Swiveling headlights increase glare on highways left curves and reduce it on right curves. Practical Applications: The procedure and conclusions of this study can contribute to develop more effective glare avoidance technologies as well as identify and assess glare-prone sections. The glare evaluation assists in evaluating glare countermeasures such as deciding whether to place a vegetation barrier and where.